2012
DOI: 10.1038/ismej.2012.133
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the minority: sulfate-reducing bacteria in an archaea-dominated subsurface biofilm

Abstract: Archaea are usually minor components of a microbial community and dominated by a large and diverse bacterial population. In contrast, the SM1 Euryarchaeon dominates a sulfidic aquifer by forming subsurface biofilms that contain a very minor bacterial fraction (5%). These unique biofilms are delivered in high biomass to the spring outflow that provides an outstanding window to the subsurface. Despite previous attempts to understand its natural role, the metabolic capacities of the SM1 Euryarchaeon remain myster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 79 publications
2
93
0
Order By: Relevance
“…We calculated the ratio of the infrared absorbance in the CH 3 region (2,990-2,945 cm À 1 ) to that of the CH 2 region (2,945-2,900 cm À 1 ) for cells from the same set of grids used for TEM analysis. Following criteria previously established 22 , we found that 97.2% ( ± 4.4%) of the spectra derived from bacteria, whereas 2.8% of the spectra (±4.4%) were non-bacterial.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…We calculated the ratio of the infrared absorbance in the CH 3 region (2,990-2,945 cm À 1 ) to that of the CH 2 region (2,945-2,900 cm À 1 ) for cells from the same set of grids used for TEM analysis. Following criteria previously established 22 , we found that 97.2% ( ± 4.4%) of the spectra derived from bacteria, whereas 2.8% of the spectra (±4.4%) were non-bacterial.…”
Section: Resultsmentioning
confidence: 54%
“…The infrared signals (in absorbance) from the energy exchange between the infrared photons and biomolecules were sampled by dividing the TEM grid in 2-mm pixels, raster scanned and processed following a method previously described elsewhere 22,54 . Cells were detected using the absorption bands of protein amide I and of lipids methyl ( À CH 3 ) and methylene ( À CH 2 À ) groups.…”
Section: Card-fishmentioning
confidence: 99%
“…Archaea have also the ability to assimilate CO 2 by at least three different fixation pathways 6 and are consequently adapted to special microbial niches out-competing their bacterial counterparts 7 . Other than niches, entire biotopes dominated by one single archaeal species are rare, and these archaea have not been studied in the past concerning their metabolic capabilities and contribution to Earth's biochemical cycles [8][9][10][11] .…”
mentioning
confidence: 99%
“…These linages often escape regular 16S rRNA gene screenings 12 and may harbor unexpected metabolic diversity and unusual cell structure 12,13,16 . An example of a genetically unexplored archaeal lineage is represented by the biofilm-forming SM1 Euryarchaeon, which has been described as a model organism for cold-loving archaea 11 . This archaeon was discovered to either live in close association with sulfide-oxidizing bacteria in sulfidic streamlets 17,18 or as an almost single species biofilm in oxygenfree subsurface aquifers [9][10][11] .…”
mentioning
confidence: 99%
“…The archaeal community at a depth of 15 m had a low diversity composed only of Group 1 Crenarchaeota, whereas the community at 80 m was composed of a diverse range of members of the Euryarchaeota (López Archilla et al 2007). In sulphate-reducing zones, archaea can form a significant proportion (Detmers et al 2004) or even the majority of the biofilm microbial community (Probst et al 2013). Flynn et al (2013) reported that distinct differences could be detected between attached and suspended archaeal communities in the Mahomet Aquifer, Illinois, and that sulphate concentration had a role in influencing the community structure.…”
Section: Global Studies Of Uncontaminated Aquifer Microbiologymentioning
confidence: 99%